PENGGUNAAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN JASMANI DI SMPN 1 KALASAN, SLEMAN - Rithaudin, Ahmad (Jurnal Pendidikan Jasmani Indonesia, 2011)
<p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 79.4pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 305.35pt; mso-height-rule: exactly;">Abstract <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">This action research was aimed to improve the learning <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">quality of the physical education by using the <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">audiovisual media in SMPN 1 Kalasan, Sleman in <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">the academic year of 2005-2006. The subject of the <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">research was the students of grade VII D SMPN 1 <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">Kalasan. The number of the students was 38 <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">students, consisted of 17 male and 21 female in the <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">academic year of 2005-2006. The subject matter of <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">learning is shooting in basket ball. The techniques <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">of the data collection of the research were <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">questionnaire, interview, and observation, while the <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">technique of the data analysis of the research was <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">descriptive. The result of research showed that <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">implementation of audiovisual media by DVD can <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">improve the student’s appreciation in learning as well <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">as enhance the student’s learning performance. The <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">suggestions to be considered are the need of <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">implementing the audiovisual as media learning in <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">large scope and different subject matter. The school <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.85pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 326.2pt; mso-height-rule: exactly;">needs special class for audiovisual media. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.8pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 612.3pt; mso-height-rule: exactly;">Kata kunci: media audiovisual, metode pembelajaran